POFELEIGHO: KASUS KAWIN LARI PADA MASYARAKAT MUNA DI KELURAHAN RAHANDOUNA KECAMATAN POASIA - Jasrun Jasrun; Wa Ode Sitti Hafsah; Laxmi Laxmi (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2018)
This study aims to find out the causes of Pofeleigho and its resolution efforts among Munanese community in Rahandouna Village, Poasia District. This study uses the theory of The Gift by Marcel Mauss. Data collection techniques are observation and in-depth interviews. The data analysis is descriptive qualitative. Data analysis is intended to simplify the data obtained in a form that is easier to read and interpret. The results show that several things that caused the occurrence of Pofeleigho in Munanese in Rahandouna Village included: (1) being pregnant out of wedlock; (2) the economic limitations of the men; (3) absence of parental consent; (4) it is not approved by the first and second wives, and (5) the application of male applications is rejected. The pofeleigho settlement process includes several stages, namely: kaforatono kamokulano robine, tanggono anahi robine we lambuno imamu, poghawangho adati or traditional meetings. The customary meetings at the pofeleigho wedding discusses several important things such as the kafoampeno adati moghane nerobine, kalentuno gholeo, customary solemnization of a marriage, and law solemnization of a marriage according to the state's marriage law. The other stage is the implementation of a family party held based on the agreement of the male and female parties to hold a crowded party or not. Keywords: cases, eloping, munanese.